Achieving Environmental Sustainability Through Hindu Ecological Spirituality - Nurhayanti, Ketut; Putra, Anggara Putu Dharma; Atmaja, I Gusti Ngurah; Utama, I Komang Sudharka (Advances In Social Humanities Research, 2025)
The South African automotive industry has undergone significant transformation from a domestically protected market to a globally integrated export-oriented sector. This paper examines the institutional and firm-level dynamics that have shaped this evolution, particularly under the Motor Industry Development Programme (MIDP) and its successor, the Automotive Production and Development Programme (APDP). The study aims to understand how industrial policies and institutional configurations interact to enable or constrain structural transformation and inclusive development. Using a qualitative case study approach, the research draws on policy documents, industry reports, and interviews with key stakeholders. Findings reveal that while policy reforms have effectively enhanced export performance and attracted foreign direct investment, they have fallen short in fostering deep supplier development, local content expansion, and technological upgrading. Moreover, institutional fragmentation and weak coordination have limited the developmental impact of these policies. The study also explores emerging challenges such as the shift toward electric vehicles and the need for green industrialization, arguing that future policy must address both competitiveness and sustainability. The research underscores the necessity of coherent institutions and localized capability building to realize inclusive industrial transformation. These insights have implications for industrial policy design not only in South Africa but also in other developing economies pursuing structural transformation in the context of global value chains and environmental imperatives.